Metal‐based nanoparticles for bone tissue engineering. (30th September 2020) - Eivazzadeh‐Keihan, Reza; Bahojb Noruzi, Ehsan; Khanmohammadi Chenab, Karim; Jafari, Amir; Radinekiyan, Fateme; Hashemi, Seyed Masoud; Ahmadpour, Farnoush; Behboudi, Ali; Mosafer, Jafar; Mokhtarzadeh, Ahad; Maleki, Ali; Hamblin, Michael R.
Abstract: Tissue is vital to the organization of multicellular organisms, because it creates the different organs and provides the main scaffold for body shape. The quest for effective methods to allow tissue regeneration and create scaffolds for new tissue growth has intensified in recent years. Tissue engineering has recently used some promising alternatives to existing conventional scaffold materials, many of which have been derived from nanotechnology. One important example of these is metal nanoparticles. The purpose of this review is to cover novel tissue engineering methods, paying special attention to those based on the use of metal‐based nanoparticles. The unique physiochemical properties of metal nanoparticles, such as antibacterial effects, shape memory phenomenon, low cytotoxicity, stimulation of the proliferation process, good mechanical and tensile strength, acceptable biocompatibility, significant osteogenic potential, and ability to regulate cell growth pathways, suggest that they can perform as novel types of scaffolds for bone tissue engineering. The basic principles of various nanoparticle‐based composites and scaffolds are discussed in this review. The merits and demerits of these particles are critically discussed, and their importance in bone tissue engineering is highlighted.